Analysis of The Influence of Subdistrict Head Leadership On Employee Performance - Yulianda Yulianda; Ivon Jalil (Ridwan Institute, 2021)
The Samatiga District Head Office is a government institution that provides services to the community. This study aims to determine the influence of the sub-district leadership on employee performance. Samatiga as many as 20 employees. The data processing of this research was carried out by interviewing and filling out questionnaires. The research method used in this study was qualitative research. Qualitative research is research which is a description of the research results obtained. The results showed that all research respondents gave the same statement that the Subdistrict Head leadership can affect employee performance. The conclusion that can be drawn in this study is that leadership is an attitude of influence where this attitude can improve the quality of work of its employees to work optimally